Iron fluoride-lithium metal batteries in bis(fluorosulfonyl)imide-based ionic liquid electrolytes - Olbrich, LF; Schart, M; Ihli, J; Xiao, AW; Matthews, G; Sanghadasa, M; Pasta, M (Cell Press, 2024)
The aviation industry's shift toward electrification demands greater energy density and enhanced cell safety compared to commercial lithium-ion batteries. Transition metal fluoride cathodes can store multiple lithium ions per metal center through a conversion reaction mechanism, resulting in a 3-fold increase in capacity compared to intercalation compounds. Additionally, fluoride cathodes exhibit remarkable thermal stability due to the ionic nature of the metal-fluoride bond. However, their practical implementation faces challenges due to their limited electronic and ionic conductivity. In this study, we conducted a comprehensive investigation of FeF2-Li metal cells in a lithium bis(fluorosulfonyl)imide N-propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide ionic liquid electrolyte. We explored the effects of FeF2 particle size, the distribution of conductive additives within the electrode, and the influence of the bis(fluorosulfonyl)imide anion on electrochemical behavior and its evolution throughout cycling. Our findings suggest that the rate requirements for electric aviation could be met at 80°C.